2020
DOI: 10.12659/msm.919311
|View full text |Cite
|
Sign up to set email alerts
|

Related Network and Differential Expression Analyses Identify Nuclear Genes and Pathways in the Hippocampus of Alzheimer Disease

Abstract: Background: Alzheimer disease (AD) is a typical progressive and destructive neurodegenerative disease that has been studied extensively. However, genetic features and molecular mechanisms underlying AD remain unclear. Here we used bioinformatics to investigate the candidate nuclear genes involved in the molecular mechanisms of AD. Material/Methods: First, we used Gene Expression Omnibus (GEO) database to obtain the expression profiles of the mRNAs from hippocampus microarray and identify differentially express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…Cross-correlations analyses of circRNAs in HuD-OE and HuD-KO mice confirmed that the expression of multiple circRNAs correlate with HuD levels in the cell. These include circRNAs from genes associated with neurodevelopmental disorders and Alzheimer’s disease, e.g., circBrwd1 and circFoxp1 ( Bacon et al, 2015 ; Quan et al, 2020 ); involved in neuronal development and regeneration, e.g., circMap1a ( Nunez and Fischer, 1997 ) and, encoding members of the Plasticity Related Genes (PRGs) and membrane-associated guanylate kinases (MAGUKs) families, e.g., circMagi1 and circLppr4 , respectively, which control synaptic development and are linked to psychiatric disorders ( Ito et al, 2012 ; Yu et al, 2015 ). Interestingly, circFoxp1 and circMap1a are part of ceRNA networks involving miRNAs, such as miR-125a-5p, which was previously associated with aging ( Makwana et al, 2017 ) and several protein-coding genes controlling neuronal polarity and cellular differentiation, such as Camsap3 and Ebf1 ( Garel et al, 1999 ; Pongrakhananon et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Cross-correlations analyses of circRNAs in HuD-OE and HuD-KO mice confirmed that the expression of multiple circRNAs correlate with HuD levels in the cell. These include circRNAs from genes associated with neurodevelopmental disorders and Alzheimer’s disease, e.g., circBrwd1 and circFoxp1 ( Bacon et al, 2015 ; Quan et al, 2020 ); involved in neuronal development and regeneration, e.g., circMap1a ( Nunez and Fischer, 1997 ) and, encoding members of the Plasticity Related Genes (PRGs) and membrane-associated guanylate kinases (MAGUKs) families, e.g., circMagi1 and circLppr4 , respectively, which control synaptic development and are linked to psychiatric disorders ( Ito et al, 2012 ; Yu et al, 2015 ). Interestingly, circFoxp1 and circMap1a are part of ceRNA networks involving miRNAs, such as miR-125a-5p, which was previously associated with aging ( Makwana et al, 2017 ) and several protein-coding genes controlling neuronal polarity and cellular differentiation, such as Camsap3 and Ebf1 ( Garel et al, 1999 ; Pongrakhananon et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Prkacb may be modified by circRNA_22673. Egfr has also been proposed as a fundamental disease-associated protein in AD pathogenesis (Quan et al, 2020;Yuen et al, 2020). They have therapeutic abilities through autophagy induction and the attenuation of reactive astrocytes (Tavassoly et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Several research studies indicated that miR-106, which is related to the dysfunction of synaptic and the AD-related cognitive deficits, might target tau-phosphorylating Fyn-kinase. [38][39][40] Another differential expression analysis on differentially expressed genes in the hippocampus of AD identified miR-106b as a hub miRNA, [41] suggesting the further role of miR-106b in neuron protection through targeting other downstream genes. Here, miR-106b inhibits the expression level of TXNIP via direct binding to its 3′-UTR, indicating that miR-106b might also contribute to the neuroprotective effect of estradiol in a TXNIP-related way.…”
Section: Effects Of Mir-106b-5p On the Proliferation And Apoptosis Of Sh-sy5y Cellsmentioning
confidence: 99%